The virtues of the vicious : Jacob Riis, Stephen Crane, and the spectacle of the slum - Gandal, Keith (New York : Oxford University Press, 1997)
In this study, the author demonstrates how, in the last decade of the 19th century, the slum became a source of spectacle as never before - in newspapers, photographs and literature. With close readings of texts by Crane and Riis, he argues that this amounted to a revolution of ethics.
Introduction; 1 Riis and Charity Writing; 2 Crane and Slum Fiction; 3 The Touristic Ethic and Photography; 4 "In Search of Excitement": The Ethics of Entertainment; 5 Self-Esteem and the Tough; 6 Psychological Moralities of the Slum; Afterword; Notes; References; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; U; V; W; Y.
Includes bibliographical references (pages 193-200) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Crane, Stephen, -- 1871-1900.; Riis, Jacob A. -- 1849-1914.; Riis, Jacob A. -- 1849-1914 -- Influence; Riis, Jacob A. -- 1849-1914; How the other half lives (Riis, Jacob A.); Maggie, a girl of the streets (Crane, Stephen); Crane, Stephen, -- (1871-1900) -- Critique et interprétation.; Riis, Jacob August, -- (1849-1914) -- Critique et interprétation.; Riis, Jacob A; Crane, Stephen; American prose literature -- 19th century -- History and criticism; Didactic literature, American -- History and criticism; Slums -- New York (State) -- New York -- Historiography; City and town life in literature; Social ethics in literature; Slums in literature; Spectacular, The; Prose américaine -- 19e siècle -- Histoire et critique; Littérature didactique américaine -- Histoire et critique; Vie urbaine dans la littérature.; Morale sociale dans la littérature.; Spectaculaire; LITERARY CRITICISM -- American -- General; American prose literature; City and town life in literature; Didactic literature, American; Influence (Literary, artistic, etc.); Slums -- Historiography; Slums in literature; Social ethics in literature; Spectacular, The; New York (State) -- New York; Slum; Geschichte; Slum; Verelendung; Alltag; Roman; USA; Villes -- Dans la littérature.; Logement insalubre -- États-Unis.; Logement insalubre -- New York (N.Y.); Littérature didactique -- Histoire et critique; Morale sociale -- Dans la littérature.; Vie urbaine -- Dans la littérature.; Littérature américaine -- Histoire et critique -- 19e siècle.; 1800-1899; Electronic books; Criticism, interpretation, etc